Római-part design strategies: a framework for designing with community and landscape - Robinson, Derek (4D Journal of Landscape Architecture and Garden Art, 2025)
The political atmosphere surrounding public space projects in Budapest is approaching a critical turning point and a paradigm shift is needed. Heavy top-down government processes ignore the needs of citizens, which can be seen in recent projects such as Varosliget and here at Római-part. Located within District III in northern Budapest, the chosen design site is shown in Figure 1. The area is approximately three kilometers long and between 200 and 300 metres wide. It is approximately 70 hectares in size. Design work is based on a typology method in which related yet distinct categories are identified for the promenade based on diverse site analyses. These typologies are then used to categorize a series of design solutions informed by research and reference projects. The result is a Design Matrix which outlines possible design solutions for each typology situation. Coinciding with this diploma work, the local community has been undertaking a process to explore their vision for the future of the area, while separately the municipal government is finalizing their own plan for a new flood protection system. This site will undergo significant change in the near future and the intent of this work is to outline many possible design solutions for each typology situation. In this way, the community can solve design challenges for the entire three kilometer shoreline in a flexible way by responding to unique situations along the promenade while still producing a unified design character. Both the process and the results of this work maybe applicable to other riverfront situations within Hungary, Central Europe and possibly further afield. The design solutions proposed in this work are ultimately searching for better ways of harmonizing social and ecological systems.